2002
DOI: 10.1055/s-2002-33088
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Severe Perineal Tear: Can We Do Better?

Abstract: Our aim was to investigate the risk factors associated with severe perineal tears defined as either third- or forth-degree tears and, ultimately, find strategies for prevention. We carried a retrospective analysis of a computerized perinatal database, collected prospectively, from a single county hospital between January 1, 1993 and June 30, 1998. Singleton vaginal vertex deliveries were analyzed for potential risk factors using univariate and multiple logistic regression analysis including all two-way interac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
2

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 14 publications
(59 reference statements)
2
34
1
2
Order By: Relevance
“…In the present trial, a sitting position was associated with more frequent episiotomies and consequently less subjects had an intact perineum. Compared to midline episiotomy, a mediolateral incision has been associated with a decreased risk of sphincter lacerations [24]; however, there is evidence suggesting that mediolateral episiotomies also substantially increase the risk of sphincter laceration during delivery [25]. In the present study, a mediolateral episiotomy was associated with grade III-IV obstetrical tears at logistic regression analysis; however, the number of sphincter tears were insufficient to allow for reliable data.…”
Section: Discussioncontrasting
confidence: 60%
“…In the present trial, a sitting position was associated with more frequent episiotomies and consequently less subjects had an intact perineum. Compared to midline episiotomy, a mediolateral incision has been associated with a decreased risk of sphincter lacerations [24]; however, there is evidence suggesting that mediolateral episiotomies also substantially increase the risk of sphincter laceration during delivery [25]. In the present study, a mediolateral episiotomy was associated with grade III-IV obstetrical tears at logistic regression analysis; however, the number of sphincter tears were insufficient to allow for reliable data.…”
Section: Discussioncontrasting
confidence: 60%
“…Larger cohort studies of perineal measurements during vaginal birth are needed to further clarify these findings. There is also considerable genetic and ethnic variation in the topography, structural morphology, and functional elasticity of the female perineum [1,2,8,11,[19][20][21]25]. Significant ethnic differences in perineal measurements were not, however, observed in our study population most likely because of the small sample size in each ethnic subgroup.…”
Section: Discussionmentioning
confidence: 63%
“…However, the value of this procedure is increasingly questioned because of the associated postoperative morbidity in the absence of clearly defined evidence for efficacy [13][14][15][16][17][18]. Paradoxically, episiotomy, particularly if median, is associated with occurrence of posterior perineal tears involving the anal sphincter in most [1,3,5,[12][13][14][15][16][17][19][20][21][22] but not all [2,[6][7][8]23] studies. Episiotomy also decreases perineal muscle strength and performance during the postpartum period more than does spontaneous posterior perineal laceration because of greater tissue disruption [4,9,16,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that episiotomies cause 3 rd and 4 th degree perineal lacerations. This situation occurs less frequently with medial lateral episiotomies [9,10]. In 9-26% of patients with median episiotomies, 3 rd and 4 th degree lacerations have been observed.…”
Section: Discussionmentioning
confidence: 99%